Larval development of Kerai lampam hybrid - Harun, Muhammad Akmal (2013)
The larval development of lemon fin barb hybrid was studied for 21 days after hatching (21 DAH). The hatching of eggs beganat 15 hours after fertilization. At hatching, larvae were transparent with the presence of the yolk sac which was bulbous on the anterior and slightly narrowed on the posterior position. The mouth began to open at 3 DAH and the yolk absorption completed at the end of the same day. On 4 DAH, the exogenous feeding started and many morphological changes occurs especially on fins, head and gut of the larvae. The lateral line was clearly visible at 13 DAH but no scale was developed even at 21 DAH. A strong relationship (BW = 1.2311TL- 3.74, R2= 0.9415) between total length and body weight of larval fish was observed.